Role of Cardiac AMP-Activated Protein Kinase in a Non-pathological Setting: Evidence From Cardiomyocyte-Specific, Inducible AMP-Activated Protein Kinase α1α2-Knockout Mice - Tokarska-Schlattner, Malgorzata; Kay, Laurence; Perret, Pascale; Isola, Raffaella; Attia, Stéphane; Lamarche, Frédéric; Tellier, Cindy; Cottet-Rousselle, Cécile; Uneisi, Amjad; Hininger-Favier, Isabelle; Foretz, Marc; Dubouchaud, Hervé; et al. (Frontiers in Cell and Developmental Biology, 2021)
AMP-activated protein kinase (AMPK) is a key regulator of energy homeostasis under conditions of energy stress. Though heart is one of the most energy requiring organs and depends on a perfect match of energy supply with high and fluctuating energy demand to maintain its contractile performance, the role of AMPK in this organ is still not entirely clear. In this work, we characterized cardiomyocyte-specific, inducible AMPK α1 and α2 knockout mice (KO), where KO was induced at the age of 8 weeks, and assessed their phenotype under physiological conditions. In the heart of KO mice, both AMPK α isoforms were strongly reduced and thus deleted in a large part of cardiomyocytes already two weeks after tamoxifen administration, persisting during the entire study period. AMPK KO had no effect on heart function at baseline, but alterations were observed under increased workload induced by dobutamine stress, consistent with lower endurance exercise capacity observed in AMPK KO mice. AMPKα deletion also induced a decrease in basal metabolic rate (oxygen uptake, energy expenditure) together with a trend to lower locomotor activity of AMPK KO mice 12 months after tamoxifen administration. Loss of AMPK resulted in multiple alterations of cardiac mitochondria: reduced respiration with complex I substrates as measured in isolated mitochondria, reduced activity of complexes I and IV, and a shift in mitochondrial cristae morphology from lamellar to mixed lamellar-tubular. A strong tendency to diminished ATP and glycogen level was observed in older animals, one year after tamoxifen administration.